André Bazin’s Film Theory: Art, Science, Religion . - Dalle Vacche, Angela (Artium Quaestiones, 2020)
Always keen on the spectators’ freedom of interpretation, André Bazin’s film theory not only asks the famous question “What is cinema?,” but it also explores what is a human. By underlining the importance of personalist ethics, Angela Dalle Vacche is the first film specialist to identify Bazin’s “anti-anthropocentric” ambition of the cinema in favor of a more compassionate society. Influenced by the personalist philosophy of his mentor, Emmanuel Mounier, Bazin argued that the cinema is a mind-machine that interrogates its audiences on how humankind can engage in an egalitarian fashion towards other humans. According to Bazin, cinema’s ethical interrogation places human spirituality or empathy on top of creativity and logic. Notwithstanding Bazin’s emphasis on ethics, his film theory is rich with metaphors from art and science. The French film critic’s metaphorical writing lyrically frames encounters between literary texts and filmmaking styles, while it illuminates the analogy between the élan vital of biology and cinema’s lifelike ontology. A brilliant analyst of many kinds of films from Europe, Asia, and Latin America, ranging from fiction to documentary, from animation to the avant-garde, Bazin felt that the abstractions of editing were as important as the camera’s fluidity of motion. Furthermore, he disliked films based on a thesis or on an a priori stance that would rule out the risks and surprises of life in motion. Neither a mystic nor an animist, Bazin was a dissident Catholic and a cultural activist without membership of a specific political party. Eager to dialogue with all kinds of communities, Bazin always disliked institutionalized religions based on dogmas.